(untitled) (Bangladesh Journal of Otorhinolaryngology, 2024)
Background: Noise remains a common environmental pollutant in industrial workplaces and has been a constant issue since the industrial revolution. Occupational hearing loss is the dominant cause of preventable sensorineural hearing loss in adults. The degree of NIHL is determined by intensity, duration of exposure, spectral characteristics of the noise, and individual susceptibility Methods: This cross-sectional study was carried out among theNassa Taipei Textile Mills Ltd. and Nassa Taipei Spinners Ltd in kachpur,Narayangonj.200 Textile workers aged from 18 to 50 years were recruited in this study. Study subjects were interviewed by trained data collector through a structured questionnaire. Environmental sound intensity level in various departments were measured using a sound level meter (Quest sound level meter, Oconomowoc WISCONSIN. Model no: 2400). Pure Tone Audiometry was done by pure tone clinical audiometer (KAMPLEX Audiometer, Model no: AC 30; Calibrated by P.C. Werth Limited in October 2004) with a frequency range of 125Hz to 8000Hzand sound intensity levels of between -10dB to 120dB was used to test each ear of the subject separately. Data was analyzed using Statistical Package for Social Sciences (SPSS) program version 26. Results: Out of 200 Textile workers whose were recruited in this study, 138(69%) were males and predominant age group was 18 to 27 years (54.5%). The prevalence of NIHL was found to be 14.5%. The most common age group was 28 to 37 years and positive association (p<.05) between hearing loss and long working hours. Non-user of PPD had little bit higher among the workers who developed hearing loss. Conclusion: The prevalence of NIHL was higher in textile industry workers. This suggests the need to provide protective gear to workers in stations generating loud noise. The prevalence was higher in male, those who experienced prolong exposure and not to used PPD. Bangladesh J Otorhinolaryngology 2023; 29(2): 89-95